PERAN ISTRI NELAYAN DALAM MENUNJANG EKONOMI KELUARGA DI DESA NANGADHERO KABUPATEN NAGEKEO - Sofia Dhengi; Veronika Wewe (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2023)
Fishermen's wives have an important role in supporting the family economy. This research aims to determine the role of fishermen's wives and their contribution to supporting the family economy. This research method is descriptive. The data used are primary and secondary. The sampling method uses a purposive sampling technique, meaning that samples are taken using certain criteria. The results of the research concluded that the role of fishermen's wives in supporting the family's economy was motivated by the husband's income being insufficient for daily needs, the uncertainty of going to sea especially when there was a lean season, namely the western season where the fish caught was very minimal, so the fishermen's wives took the initiative to take Her roles include drying fish, selling ice cubes, selling cakes and selling fish caught by her husband. With direct involvement, fishermen's wives can make a big contribution to their families with the highest income contribution of fishermen's wives being as fish sellers, namely 94%, meaning that fishermen's wives have a very important role in increasing the family's economic income, where fishermen's wives' income as fish sellers is more larger than the income of fishermen's wives in other fields.